2019
DOI: 10.1021/acs.jpcb.9b05869
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring A51V Variant of Human Cytochrome c Destabilizes the Native State and Enhances Peroxidase Activity

Abstract: The A51V variant of human cytochrome c is linked to thrombocytopenia 4 (THC4), a condition that causes decreased blood platelet counts. A 1.82 Å structure of the A51V variant shows only minor changes in tertiary structure relative to the wild-type (WT) protein. Guanidine hydrochloride denaturation demonstrates that the global stability of the A51V variant is 1.3 kcal/mol less than that of the WT protein. The midpoint pH, pH1/2, of the alkaline transition of the A51V variant is 1 unit less than that of the WT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 94 publications
4
24
0
Order By: Relevance
“…No differences in the far-UV CD profiles for the WT or any of the variants in a temperature range between 10 and 30 o C were observed (data not shown). The X-ray structures of the three variants, [5,42,48], reveal no significant secondary structure differences in respect to the WT structure. [23] In contrast, solution NMR studies indicate that the G41S and Y48H variants are more dynamic than the WT protein.…”
Section: Far-uv CD Spectroscopy Of the Ferric A51v Variant And Comparmentioning
confidence: 87%
“…No differences in the far-UV CD profiles for the WT or any of the variants in a temperature range between 10 and 30 o C were observed (data not shown). The X-ray structures of the three variants, [5,42,48], reveal no significant secondary structure differences in respect to the WT structure. [23] In contrast, solution NMR studies indicate that the G41S and Y48H variants are more dynamic than the WT protein.…”
Section: Far-uv CD Spectroscopy Of the Ferric A51v Variant And Comparmentioning
confidence: 87%
“…As noted above, the ssNMR data identify increased mobility not only in membrane-facing regions, but also in other segments such as loop C. Thus, it is possible that loop C dynamics play a role in the activation of cyt c’s peroxidase function. This kind of role is supported by recent studies of cyt c mutants showing that mutations in loop C can also regulate cyt c peroxidase activity [9092]. Lei et al determined the X-ray crystal structure of the A51V variant of cyt c, which shows only minor changes in tertiary structure compared to the WT protein, but exhibits several folds of increase in peroxidase activity [90].…”
Section: Discussionmentioning
confidence: 92%
“…This kind of role is supported by recent studies of cyt c mutants showing that mutations in loop C can also regulate cyt c peroxidase activity [75][76][77]. Lei et al determined the structure of a A51V variant of cyt c, which shows only minor changes in tertiary structure compared to the WT protein, however, exhibits several folds of increase in peroxidase activity [75]. A G41T mutation causes increased mobility of both loops C and D, resulting in loop D destabilization [77].…”
Section: On Lipid-induced Allosteric Mobility Affecting Cyt C Loop Cmentioning
confidence: 90%
“…De Rocco et al reported that the p. Gly42Ser and p.Tyr49His variants in yeast and mouse cellular models were responsible of the diminished respiratory level and increased apoptotic rate ( De Rocco et al, 2014 ). Lei et al showed that the Ala51Val variant enhanced peroxidase activity by destabilizing the native state of Cyt-c, and all three variants Gly42Ser, Tyr49His, and Ala51Val had reduced global and local stability than that of wild type Cyt-c ( Lei and Bowler, 2019 ). Moreover, Uchiyama et al provided that the mutation of p.Lys301del could significantly reduced cytochrome c protein expression and cause functional defects in the mitochondrial respiratory chain ( Uchiyama et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%